Deuteronomy for the church : who we are, what God requires - Boring, M. Eugene (Fortress Press, 2022)
"Justice, only justice" is Deuteronomy's terse summary of what Yahweh requires of the people of God. What Deuteronomy reveals is that the competence to be God's people, to know God, and to do God's will comes only through hearing the transforming Word of God in Scripture. Deuteronomy sets the scene for hearing God's Word in the wilderness as Moses addresses a new, in-between generation of "all Israel." The people of God are no longer in Egypt, nor yet in Canaan. Moses warns them against allowing the past to control them and attempts to equip them to live faithfully in the new situation in which they find themselves. Deuteronomy's core theology, expressed in the Shema ("Hear, O Israel: The Lord is our God, the Lord alone"), forms the structure of the book: What does it mean to "hear"? Who is "all Israel"? And how does the identity of the one Lord shape ethics? To hear the biblical text does not mean passive listening. Hearing means engaging the story of God's Word with our own story. The book explores the three levels of hearing in Deuteronomy: hearing the story in the text--its narrative world; hearing the story behind the text--what really happened; and hearing the story of the text--how the original preaching and teaching became a canonical book that comes to us already translated with a rich history of interpretation in which contemporary readers stand. Deuteronomy for the Church reminds us that Christian believers are included in "all Israel," that in reading Deuteronomy we are not merely spectators overhearing what was once said to other people, but that we are addressed as on-stage participants in the story, with the responsibility to discern and improvise what God requires of us in our time and place. Discerning the will of God means deepening our understanding of God's own revelation of the divine character and purpose in history. This responsibility is illuminated by New Testament examples that interpret Deuteronomyin light of God's definitive self-revelation in Christ.